Comparison of long-term efficacy and safety of blonanserin treatment in individuals with first-episode and relapsed schizophrenia: a 3-year retrospective study. Issue 4 (2nd October 2019) - Huh, Lyang; Lee, Bong Ju
ABSTRACT: Purpose: The objective of this retrospective chart review study was to evaluate the long-term efficacy and tolerability of blonanserin treatment in individuals with schizophrenia. Patients and methods: We collected data from 28 (56%) antipsychotic-naïve subjects with first-episode (FE) schizophrenia and 22 subjects with relapsed schizophrenia treated with blonanserin. We investigated psychiatric hospitalization and medication discontinuation rates, Positive and Negative Syndrome Scale (PANSS) scores, Clinical Global Impression–Severity (CGI-S) scale scores, body mass index (BMI) at baseline to endpoint and laboratory tests including serum prolactin, total cholesterol (TC), low-density lipoproteins (LDL), high-density lipoproteins (HDL), triglycerides (TG), and glucose. Additionally, we measured the differences between the two groups and overall changes in levels. Results: Thirty-one subjects received blonanserin for 3 years. Signiﬁcant improvements in psychiatric symptoms from baseline to endpoint were observed individuals with schizophrenia who received blonanserin treatment. There were remarkable changes in PANSS and CGI-S scores between baseline and those measured after 3 years ( p < .01) in both groups; the FE schizophrenia group demonstrated better improvement as reflected by clinical changes assessments. Compared to baseline values, the endpoint measurements showed no statistical differences in terms of serum prolactin, glucose, or LDL and HDL cholesterol ( p > .05) in both groups. After 3 years of treatment, there was a statistically significant increase in TC and TG with only a minimal increase in BMI ( p < .05). However, there were no statistical differences between the two groups. Conclusion: Blonanserin is useful for the maintenance treatment of schizophrenia due to its therapeutic efficacy; moreover, it does not induce hyperprolactinaemia, significant weight gain, or cause problematic endocrine effects. Its strength might be attributed to its unique pharmacological properties.